Implementation of Sensor Fusion for Inertia Measurement Using Kalman Filter on Hexacopter - Afdhal Akrom, Huda Ubaya , (PROCEEDING IC-ITECHS 2014, 2014)
Tilt angle is an important parameter in the flying robot to keep stability while airborne. The tilt angle was measured using Inertial Measurement Unit (IMU). The IMU consists of two sensors, the accelerometer and gyroscope. Each data from these sensors have noise that caused an error measurements. So that, it is needed a combination of sensor data to make a precision and acuracy data.Therefore, the author tries to combine accelerometer and gyroscope (sensor fusion) using a kalman filter algorithm that is implemented on Micro Hexacopter to obtain accurate data in regulating stability while airborne.